Baggage Delivery Time and Its Impact on Garuda Indonesia Passenger Satisfaction - Roni Gusman; Setyamartana Parman (Sekolah Tinggi Teknologi Kedirgantaraan, 2025)
This study aims to analyze the effect of Baggage Delivery Time (BDT) on passenger satisfaction with Garuda Indonesia at Sultan Syarif Kasim II Airport, Pekanbaru. The background of this research is based on the importance of post-flight services, particularly the speed of baggage delivery, as one of the key indicators of airline service quality that influences passengers’ final impressions. The research employed a quantitative approach using a survey and observational design. BDT data were obtained through direct observation of ground handling performance over four days of flights, while passenger satisfaction data were collected through questionnaires completed by 98 respondents. Data analysis was conducted using simple linear regression, t-test, and coefficient of determination (R²) with the aid of SPSS. The results showed that BDT has a positive and significant effect on passenger satisfaction, with a significance value of 0.035 (<0.05) and an R² of 0.045 (4.5%). These findings confirm that the faster the baggage delivery time, the higher the level of passenger satisfaction. The study recommends improving coordination between the airline and ground handling, optimizing conveyor belt facilities and Ground Support Equipment (GSE), and implementing a real-time baggage delivery monitoring system. Future research is suggested to include other variables such as staff communication quality and airport facility conditions.